‫تأثير‬‫مبادئ‬ ‫حوكمة‬ ‫الشركات‬ ‫على‬ ‫أخلاقيات‬ ‫العمل‬ ‫للمؤسسة‬ ‫الإقتصادية‬ ‫دراسة‬‫حالة‬ ‫سونلغاز‬ - سلمى ‫زمال ‬‫‬; ‬‫سلمى ‫ذوايبية ‬ (My University, 2018)
This study focuses on the presentation of the principles of corporate governance on the ethics of work in the economic institution based on secondary data from memories, books, magazines and previous studies on corporate governance, work ethics and preliminary data using observations to complete the study concluded that it there is a correlation between corporate governance principles and the application of ethics Business . The main suggestions of this study are that the application of ethical values ​​and governance principles play an important role in achieving an environment of healthy work. the study focuses on the impact of corporate governance principles on the ethics of work to the Sonalgaz Foundation and the extent to which these principles contribute to its consolidation.